Donkey Fascioliasis Within a One Health Control Action: Transmission Capacity, Field Epidemiology, and Reservoir Role in a Human Hyperendemic Area - Mas-Coma, Santiago; Buchon, Paola; Funatsu, Ilra R.; Angles, Rene; Mas-Bargues, Cristina; Artigas, Patricio; Valero, M. Adela; Bargues, M. Dolores (Frontiers in Veterinary Science, 2020)
A One Health initiative has been implemented for fascioliasis control in a human hyperendemic area for the first time. The area selected for this multidisciplinary approach is the Northern Bolivian Altiplano, where the highest prevalences and intensities in humans have been reported. Within the strategic intervention axis of control activities concerning animal reservoirs, complete experimental studies and field surveys have been performed to assess the fascioliasis transmission capacity and epidemiological role of the donkey for the first time. Laboratory studies with altiplanic donkey-infecting Fasciola hepatica and altiplanic Galba truncatula snail vector isolates demonstrate that the donkey assures the viability of the whole fasciolid life cycle. Several aspects indicate, however, that F. hepatica does not reach, in the donkey, the level of adaptation it shows in sheep and cattle in this high altitude hyperendemic area. This is illustrated by a few-day delay in egg embryonation, longer prepatent period despite similar miracidial infectivity and shorter patent period in the intramolluscan development, lower cercarial production per snail, different cercarial chronobiology, shorter snail survival after shedding end, shorter longevity of shedding snails, and lower metacercarial infectivity in Wistar rats. Thus, the role of the donkey in the disease transmission should be considered secondary. Field survey results proved that liver fluke prevalence and intensity in donkeys are similar to those of the main reservoirs sheep and cattle in this area. Fasciolid egg shedding by a donkey individual contributes to the environment contamination at a rate similar to sheep and cattle. In this endemic area, the pronounced lower number of donkeys when compared to sheep and cattle indicates that the epidemiological reservoir role of the donkey is also secondary. However, the donkey plays an important epidemiological role in the disease spread because of its use by Aymara inhabitants for good transport, movements and travel from one locality/zone to another, a repercussion to be considered in the present geographical spread of fascioliasis in the Altiplano due to climate change. Donkey transport of parasite and vector, including movements inside the zone under control and potential introduction from outside that zone, poses a problem for the One Health initiative.